The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0091552119852161
|View full text |Cite
|
Sign up to set email alerts
|

Over 40%: Asian Americans and the Road(s) to Community Colleges

Abstract: Objectives: What are some of the key reasons Asian American students enroll in community colleges? Method: We utilized qualitative methods, conducting 49 interviews in Southern California with current Asian American community college and transfer students at three institutions. Results: We identified five key reasons why Asian American participants attended community college: cost, strategy, lack of intentionality in college planning, lack of support and accurate information, and needing a second chance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Researchers have examined how students' social class can affect their likelihood to transfer (Dowd et al, 2013;Eddy et al, 2006); how community colleges can perpetuate social stratification (Dougherty, 1987;Dougherty & Kienzl, 2006;Dowd & Melguizo, 2008;Karabel, 1972Karabel, , 1974Schudde & Goldrick-Rab, 2015); and how financial knowledge influences students' trajectories (e.g., Campbell et al, 2015;Carales, 2020;Dowd et al, 2013;Goldrick-Rab, 2006;Park & Assalone, 2019;Wells, 2008). Their studies have found that students from higher socioeconomic classes are more likely to transfer and persist in higher education.…”
Section: Understandings Of Financing Their Educationmentioning
confidence: 99%
“…Researchers have examined how students' social class can affect their likelihood to transfer (Dowd et al, 2013;Eddy et al, 2006); how community colleges can perpetuate social stratification (Dougherty, 1987;Dougherty & Kienzl, 2006;Dowd & Melguizo, 2008;Karabel, 1972Karabel, , 1974Schudde & Goldrick-Rab, 2015); and how financial knowledge influences students' trajectories (e.g., Campbell et al, 2015;Carales, 2020;Dowd et al, 2013;Goldrick-Rab, 2006;Park & Assalone, 2019;Wells, 2008). Their studies have found that students from higher socioeconomic classes are more likely to transfer and persist in higher education.…”
Section: Understandings Of Financing Their Educationmentioning
confidence: 99%